(untitled) (Revista Puertorriqueña de Psicologia, 2016)
Through bringing together literature on identity work, participatory action research, and critical literacy, the current study examines the identity work of low-income and working class youth of color (predominantly Latinx) as they confronted obstacles in their efforts to enact school change. Within a youth participatory action research (yPAR) program, youth created a mural to represent community members’ stories about times they felt they did or did not have the power to change something in their community. Research questions were: (1) How might yPAR serve as a context for children’s identity work? And (2), how do children in a yPAR program respond to obstacles in their efforts to perform identities as social change agents? Results examine the process of mural symbol creation and are based on analyses of ethnographic field notes from 13 program meetings. Through encounters, youth engage with power as it relates to their social identities in the following: yPAR serves as a context for children’s identity work by providing them a space where they can co-construct critical engagement, and read identity and power in text and images. They respond to obstacles by critically engaging with conflict, and performing change agent identities.